Pathology and causes of death of stranded cetaceans in the southwestern coast of Spain (2001-2004) - de la Fuente, Jesús; Arbelo Hernández, Manuel Antonio; Carrasco, Librado; Fernández Rodríguez, Antonio Jesús (2011)
Toe southwest coast of Andalusia (Spain) is an area of frequent presence of cetaceans. Seventeen different cetacean species have been reposted to strand until now. In order to establish an approximation to the pathology and causes of death of these animals, forty-eight stranded cetaceans were studied between 2001 and 2004 in this area. The animals analyzed were: fifteen common dolphins (Delphinm de/phis), eight striped dolphins (Stene/la coeruleoa/ba), seven bottlenose dolphins (forsiops truncatus), six minke whales (Balaenoptera acutorostrata), five harbour porpoises (Phocoena phocoena), two fin whales (Balaenoptera physalus), one sperm whale (Physeter macrocephalus), one long :finned pilot whale (Globicephala melas) and three unidentified delphinids. The study was perfonned using a systematic standardized necropsy and histopathological protocol. Due to decomposition status of the carcasses, a complete or partía! necropsy was done to twenty-five animals (52,08%), and samples were collected from twenty-three of them (47,92%) for its microscopic study. Cause/s of death (defined as pathological entity/ies) of twenty-five cetaceans were established. Most of these animals (84%) were diagnosed as natural pathological entities, that included consumptive (44%), non consumptive (24%), neonatal/perinatal (12%) and intra-interspecific traumatic (4%) pathologies. The most frequently observed lesions were those related to infectious and parasitic diseases, associated wíth active stranding and/or with aging animals. The remaining animals were diagnosed wíthin the anthropogenic ori1:,,in pathological entities (15,38%), that included fishing interaction (12%) and ship collisions (4%). This study supports the great utility of pathological studies in stranded animals for the assessment of cetacean health along the spanish coasts.